2012
DOI: 10.1590/s1516-35982012000800023
|View full text |Cite
|
Sign up to set email alerts
|

Testicular echotexture and seminal quality of young Montana Tropical Compound bulls classified as sound and unsound for breeding

Abstract: -The objective of this study was to investigate the relationship between testicular echotexture and seminal quality, in addition to evaluate the testicular parenchyma echogenicity pattern in young Montana bulls classified as sound and unsound for breeding. Fifty-two young Montana Tropical Compound bulls from 22 to 33 months of age were used. The animals were previously evaluated by breeding soundness evaluation and thereafter divided into two groups of breeding soundness classes: 1 = 16 animals sound for breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…(2015) showed that mean testicular heterogeneity was positively correlated with the total spermatozoal output. However, other researchers did not find a correlation between pixel intensity and sperm production or semen quality in dogs (Dias et al., 2017; Pinho et al., 2012; Tomlinson et al., 2017). Many researchers have reported that testicular echogenicity increases during sexual development directly with seminiferous tubules growth (Camela et al., 2018; Hamm & Fobbe, 1995; Pozor et al., 2017; Silva et al., 2012).…”
Section: Discussionmentioning
confidence: 92%
“…(2015) showed that mean testicular heterogeneity was positively correlated with the total spermatozoal output. However, other researchers did not find a correlation between pixel intensity and sperm production or semen quality in dogs (Dias et al., 2017; Pinho et al., 2012; Tomlinson et al., 2017). Many researchers have reported that testicular echogenicity increases during sexual development directly with seminiferous tubules growth (Camela et al., 2018; Hamm & Fobbe, 1995; Pozor et al., 2017; Silva et al., 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Kastelic et al (2001) reported an intensity of 158.5 while working with Angus cattle, and Carmo et al (2012) analysed Guzerat cattle that were 21-24, 24.1-27, and 27.1-30 months old and obtained values of 102.3, 112.0, and 127.5, respectively. Pinho et al (2012) worked with Montana cattle, obtaining values of 95.7 and 94.0 for animals that could and could not reproduce, respectively. Finally, Cardilli et al (2012) worked with sexually mature 18 month old Nelore bulls and obtained a value of 115.3.…”
Section: Resultsmentioning
confidence: 99%
“…Testicular echogenicity was obtained from the grayscale of pixels (0–255), where the minimum numbering (0) equaled the black tone pixel and the maximum numbering (255) equaled the white tone pixel, as previously described [ 46 , 47 ]. The analyses were performed in the sagittal (longitudinal) plane.…”
Section: Methodsmentioning
confidence: 99%